Phenotypic and genotypic characteristics of Iranian soft rot bacteria isolates from different hosts - REZAEI, Rasool; TAGHAVI, S. Mohsen (Phytopathologia Mediterranea, 2010)
During 2005–2006, 42 soft rot bacterial strains were isolated from the infected tubers of potato, roots of carrot, sugar beet and turnip, and the leaves of lettuce and cabbage with soft rot symptoms in Iran. The isolates were rod-shaped, motile with peritrichous flagella, gram negative, facultative anaerobe, oxidase and urease negative and they rotted potato tuber slices. Of the 42 isolates, 20 were identified as Pectobacterium carotovorum subsp. carotovorum (Pcc), 6 as P. carotovorum subsp. odoriferum (Pco), 4 as P. betavasculorum (Pb) and 12 strains as Dickeya dadantii (Dda). PCR amplification of fingerprints of repetitive bacterial DNA elements using the REP, ERIC and BOX primers differentiated the soft rot bacteria to the species and subspecies level. Strains of Pcc and Dda were phenotypically and genotypically highly variable, but Pb and Pco strains had low variability. REP-PCR was found to be a promising genotypic tool for the rapid and reliable speciation and typing of soft rot bacteria.